Perception of Chilean teachers of Professional Technical establishments on entrepreneurship, innovation and gamification (2024)
The research objective considered examining the perception of chilean teachers about entrepreneurship, innovation and gamification through a non-experimental study of a transversal nature, with a quantitative approach and a descriptive-correlational scope. 106 teachers from six educational establishments were surveyed through a Likert-type questionnaire and a comparative analyzes of mean differences were carried out through ANOVA, t-tests, and Pearson was used to examine the relationships between variables and sociodemographic data. The main findings support the idea that the promotion of innovation, entrepreneurship and gamification in education should not be considered in isolation, but rather as complementary components that can strengthen each other to enrich the teaching-learning process and encourage the development of essential skills in students. It is concluded that there is a solid commitment to innovation in teaching, but it is necessary to consider improvements in the field of entrepreneurship and gamification.